Poimenovanja argumentacije v referenčnem korpusu FidaPLUS - Dukić, Davorin (Jezik in slovstvo, 2009)
With an analysis of authentic text extracts in the FidaPLUS Slovene language reference corpus, the article determines whether Slovene speakers are aware of the difference in meaning between argumentation, (logical) demonstration and (rhetorical) persuasion, as explained in a short overview of the theoretical concepts. The use of designations for the three language activities mentioned is surveyed, with the goal of ascertaining whether it is a case of synonymous or non-synonymous use. The research shows that the level of awareness of the differences between these three related language activities is, judging by the use of their designations, at a low level.
Keywords: argumentacija; Corpus linguistics; FidaPLUS; korpusno jezikoslovje; referenčni korpus; Slovene; Slovenian National Corpus; slovenščina